2004
DOI: 10.1111/j.1527-5299.2004.01328.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Angiotensin‐Converting Enzyme Polymorphism in Congestive Heart Failure

Abstract: Angiotensin‐converting enzyme (ACE) is a zinc metallopeptidase, with primary known functions of converting angiotensin I into the vasoactive and aldosterone‐stimulating peptide angiotensin II and inactivating bradykinin. There is high variability among individuals in ACE concentrations, mainly due to the presence of a genetic polymorphism. The ACE gene has, in fact, insertion/deletion polymorphism in intron 16, consisting of a 287‐base pair Alu repeat sequence, with three genotypes: insertion polymorphism, ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 51 publications
(71 reference statements)
0
6
0
1
Order By: Relevance
“…3 Table 6 summarizes previous studies that are related to ACE genotype associations. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] In the present study, we investigated the possible association of ACE I/D polymorphisms with the development of GDM among selected individuals from the Asian Indian population. The study was carried out between two groups (GDM cases and non-GDM subjects) and showed significant differences with respect to age, weight and PPBG.…”
Section: Discussionmentioning
confidence: 99%
“…3 Table 6 summarizes previous studies that are related to ACE genotype associations. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] In the present study, we investigated the possible association of ACE I/D polymorphisms with the development of GDM among selected individuals from the Asian Indian population. The study was carried out between two groups (GDM cases and non-GDM subjects) and showed significant differences with respect to age, weight and PPBG.…”
Section: Discussionmentioning
confidence: 99%
“…ACE is involved in both vascular function as well as ventricular muscle growth [15]. Previous studies have estimated that genetic variation accounts for approximately 50% of the total variance in serum ACE levels in humans [16]. The most prominent polymorphism of the gene that encodes ACE is a 287 bp insertion/deletion segment (I/D) in intron 16.…”
Section: Variation In the Genes That Encode Proteins Of The Raas And mentioning
confidence: 99%
“…In the last 5 years, the effects of a common variation in the DNA sequence, single nucleotide polymorphisms (SNPs) in candidate genes in HF have been reviewed and summarized by several authors. [16][17][18][19][20] These reviews suggest that there is evidence that genes play a role in the pathophysiology of HF. Most studies report that many SNPs may have a modest effect on HF outcomes.…”
Section: Genetic Testing and Cardiomyopathymentioning
confidence: 99%
“…However, standardized pharmacologic treatment leads to marked variability in clinical outcome. 18,23 Recently, pharmacogenetic data for b-blockers in patients with HF and potential implications of b-blocker pharmacogenetics for HF patients have also been summarized by several authors. 24,25 It is suggested that the ADRB 1 Ar-g389Gly polymorphism might predict responsiveness to b 1 -adrendric receptor agonists and blockers: individuals homozygous for the Arg389 polymorphism may be good responders, while those homozygous for Gly389 may be poor or nonresponders.…”
Section: Pharmacogeneticsmentioning
confidence: 99%